THE CORRELATION BETWEEN COGNITIVE STRATEGIES AND STUDENTS’ READING COMPREHENSION OF ELEVENTH GRADE AT SMK NEGERI 2 NGANJUK - REZA OKTAVIANTI (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2019)
ABSTRACT The purpose of this study is to know whether or not there is significant correlation between cognitive strategies and students’ reading comprehension of the eleventh grade students. This research design is quantitative which is used to investigate the correlation between cognitive strategies and students’ reading comprehension of the eleventh grade of SMK Negeri 2 Nganjuk. The sample is class 11 KU 1 consisting of 32 students. Data was collected by using two kinds of instrument, reading test and questionnaire. Based on the result of this research, it is found that the use of cognitive strategies influence the reading comprehension of the eleventh grade students. It is also supported by the result of the data which has been computed by the formula of Pearson Product Moment that the score of rxy (0,1678) is higher than rxy–table in significant 1% (0,449) and 5% (0,349). Finally, the writer concludes that there is significant correlation between students’ cognitive strategies and students’ reading comprehension. Cognitive strategies give significant influence for students’ reading comprehension. Furthermore, It is hoped that this research will be useful for the English teacher in guiding the students about how to use cognitive strategies in reading. KEYWORDS: Correlation, Cognitive Strategies and Reading Comprehension ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui ada tidaknya hubungan yang signifikan antara strategi kognitif dan pemahaman membaca siswa kelas sebelas. Desain penelitian ini adalah kuantitatif yang digunakan untuk mengetahui hubungan antara strategi kognitif dan pemahaman membaca siswa kelas sebelas SMK Negeri 2 Nganjuk. Sampelnya adalah kelas 11 KU 1 yang berjumlah 32 siswa. Pengumpulan data dilakukan dengan menggunakan dua jenis instrumen, tes membaca dan angket. Berdasarkan hasil penelitian ditemukan bahwa penggunaan strategi kognitif mempengaruhi pemahaman membaca siswa kelas sebelas. Hal ini juga didukung oleh hasil data yang telah dihitung dengan rumus Product Moment dari Pearson bahwa nilai rxy (0,1678) lebih tinggi dari rxy – tabel pada signifikansi 1% (0,449) dan 5% (0,349). . Akhirnya, penulis menyimpulkan bahwa ada hubungan yang signifikan antara strategi kognitif siswa dan pemahaman bacaan siswa. Strategi kognitif memberikan pengaruh yang signifikan terhadap pemahaman bacaan siswa. Lebih lanjut, penelitian ini diharapkan bermanfaat bagi guru bahasa Inggris dalam membimbing siswa tentang bagaimana menggunakan strategi kognitif dalam membaca. KATA KUNCI: Korelasi, Strategi Kognitif dan Pemahaman Membaca